2010
DOI: 10.1159/000316885
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Paroxysmal Atrial Fibrillation in Acute Stroke Patients

Abstract: Background: Atrial fibrillation (AF) is a frequent cause of stroke, but detecting paroxysmal AF (pAF) poses a challenge. We investigated whether continuous bedside ECG monitoring in a stroke unit detects pAF more sensitively than 24-hour Holter ECG, and tested whether examining RR interval dynamics on short-term ECG recordings using an automated screening algorithm (ASA) for pAF detection is a useful tool to predict the risk of pAF outside periods of manifest AF. Methods: Patients >60 years with acute ischemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 64 publications
5
61
1
5
Order By: Relevance
“…42 In comparison with standard telemetry, monitors with software algorithms for automatic detection of AF (5.4% versus 7.7%) 45 or a systematic analysis of saved data from recordings (2.6× increase) seemed to improve detection rates.…”
Section: Patient Selection and Duration Of Monitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…42 In comparison with standard telemetry, monitors with software algorithms for automatic detection of AF (5.4% versus 7.7%) 45 or a systematic analysis of saved data from recordings (2.6× increase) seemed to improve detection rates.…”
Section: Patient Selection and Duration Of Monitoringmentioning
confidence: 99%
“…42 In comparison with standard telemetry, monitors with software algorithms for automatic detection of AF (5.4% versus 7.7%) 45 or a systematic analysis of saved data from recordings (2.6× increase) seemed to improve detection rates. 25 Higher detection rates were also seen in the selected group (8 studies; Figure 3) compared with the unselected group (6 studies; Figure 2) using 24-hour Holter monitoring.…”
Section: Patient Selection and Duration Of Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Besides its main original goal to detect life-threatening arrhythmia, it was suggested that cardiac telemetry facilitates the diagnosis of paroxysmal AF, too. [15][16][17][18] However, the superiority of continuous monitoring for AF detection over serial ECG assessments was questioned by a study on 150 consecutive patients admitted to a Canadian stroke unit. 11 On average, 2.4 ECGs were conducted during inpatient evaluation.…”
Section: Serial Ecg Assessments Versus Continuous Monitoringmentioning
confidence: 99%
“…Previous investigations, however, indicate that 24-hour Holter ECG has low impact for AF detection during the acute phase of ischemic stroke 12 and that it is clearly inferior to routine stroke unit monitoring. 17 Although Holter recordings have been conducted in clinical routine in a subset of our study cohort, the data did not allow a systematic head-to-head comparison of 24-hour Holter ECG and SEA-AF. Because all steps of SEA-AF were performed and analyzed together, we cannot provide data on performance and value of single steps within the algorithm.…”
Section: Limitationsmentioning
confidence: 99%